Evaluation of a Novel Immunoassay for Quantification of C1q for Clinical Diagnostic Use - Sandholm, Kerstin; Persson, Barbro; Skattum, Lillemor; Eggertsen, Gösta; Nyman, Dag; Gunnarsson, Iva; Svenungson, Elisabet; Nilsson, Bo; Ekdahl, Kristina N. (Frontiers in Immunology, 2019)
Objectives: C1q is a valuable biomarker of disease activity in systemic lupus erythematosus (SLE). The “gold standard” assay, rocket immunoelectrophoresis (RIE), is time-consuming, and thus a shift to soluble immune precipitation techniques such as nephelometry has occurred. However, quantification of C1q with these techniques has been questioned as a result of the antibody binding properties of C1q. In the present work, we have compared results using various techniques (RIE, nephelometry, and ELISA) and have developed and validated a new magnetic bead-based sandwich immunoassay (MBSI). Methods: C1q was quantified by nephelometry and the new sandwich immunoassay in 45 serum samples analyzed using RIE. C1q was also assessed in plasma using RIE and sandwich immunoassay in samples from SLE patients with nephritis (n=69), SLE patients without nephritis (n=310) as classified by BILAG score, and matched controls (n=322). In addition, cerebrospinal fluid (CSF) samples from 31 patients, previously analyzed with ELISA, were also analyzed with the MBSI to test the behavior of this new assay in the lower detection range. Results: We found a strong correlation between the new MBSI, RIE, and ELISA, but not with nephelometry. The MBSI demonstrated lower levels of C1q in SLE patients than in matched controls (p<0.0001), and patients with nephritis had lower levels than patients without nephritis (p<0.01). Similarily, RIE showed significant differences between the patient groups (p<0.0001). An association was also found between the levels of C1q and the SLE disease index (SLEDAI). Furthermore, there was good correlation between the values obtained by MBSI and ELISA, in both serum (r=0.960) and CSF (r=0.786), underscoring the ability of both techniques to measure low concentrations of C1q with high accuracy. Conclusion: The sandwich immunoassay correlated well with RIE, but soluble immune precipitation techniques, such as nephelometry, did not appear suitable alternatives, since C1q itself, and possibly anti-C1q antibodies, interfered with the measurements. The new sandwich immunoassay is therefore a good replacement for RIE in monitoring SLE disease activity.